Fuzzy Control of the Robotic Hands Catching Force Using Muscle Wires Actuator - Al-Azzawi, Yarub Omer Naji (Al-Khwarizmi Engineering Journal, 2011)
The aim of this research is controlling the amount of the robotic hand catching force using the artificial muscle wire as an actuator to achieve the desired response of the robotic hand in order to catch different things without destroying or dropping them; where the process is to be similar to that of human hand catching way. The proper selection of the amount of the catching force is achieved through out simulation using the fuzzy control technique. The mechanism of the arrangement of the muscle wires is proposed to achieve good force selections. The results indicate the feasibility of using this proposed technique which mimics human reasoning where as the weight of the caught peace increases, the force increases also with approximately the same amount of increment.